Weed growth, herbicide efficacy, and rice productivity in dry seeded paddy field under different wheat stubble management methods - Muhammad Zia-Ul-Haq; Abdul Khaliq; Sheng QIANG; Amar Matloob; Saddam Hussain; Saba Fatima; Zeshan Aslam (Journal of Integrative Agriculture, 2019)
To ascertain the influence of wheat stubble management options and chemical weed control methods on weed growth and productivity of dry direct-seeded fine rice, a two years' field study was undertaken at the Agronomic Research Farm, University of Agriculture, Faisalabad, Pakistan in 2013 and 2014. Different wheat stubble management methods, viz., incorporation, burning and retention were executed during seed-bed preparation. While, herbicide treatments comprised of a weed check, weed free, pendimethalin followed by tank mixture of fenoxaprop p-ethyl+ethoxysulfuron ethyl, and bispyribac sodium followed by tank mixture of fenoxaprop p-ethyl+ethoxysulfuron ethyl. Results revealed that weed control efficacy of both herbicide treatments ranged from 84 to 94%. Herbicide treatments significantly reduced weed density (88–90%) and dry weight (86–88%), while improved the rice growth attributes compared with weed check. Application of bispyribac sodium followed by tank mixture of fenoxaprop p-ethyl+ethoxysulfuron ethyl in stubble retention recorded 226 and 273% increase in kernel yield over weedy check in 2013 and 2014, respectively. In stubble incorporation, pendimethalin followed by tank mixture of fenoxaprop p-ethyl+ethoxysulfuron ethyl was more effective in increasing (256–293%) rice yields over weedy check. Among different treatment combinations, the maximum net benefits (1397.49–1472.22 USD ha−1), net returns (636–700 USD ha−1), benefit cost ratio (1.77–1.83) and marginal rate of return (2187–2330%) were recorded with the application of bispyribac sodium followed by fenoxaprop p-ethyl+ethoxysulfuron ethyl in stubble retention. In crux, application of bispyribac sodium followed by tank mixture of fenoxaprop p-ethyl+ethoxysulfuron ethyl in stubble retention is efficient approach to control weeds, and get maximum rice productivity and net economic returns under dry seeded system.